Sebaran logam berat terlarut di Perairan Teluk Jakarta - Maisalda, Dwianka Rahman; Yonvitner, Yonvitner; Effendi, Hefni (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Jakarta Bay is an active area and receives pollution from the mainland through 13 river systems in DKI Jakarta. This waste enters Jakarta Bay through 13 rivers. This study compared the distribution of dissolved heavy metals in the West and East Monsoons of Jakarta Bay to understand the processes and sources of heavy metals. Sampling was carried out once in each zone, and sea water samples stored in HDPE (high-density polyethylene) bottles were taken to the laboratory for analysis using AAS (Atomic Absorption Spectrophotometry), with a measurement accuracy of 0.001 mg/L. GIS was used to map heavy metal parameters. The concentrations of heavy metals found were mercury (Hg) 0.0002 to 0.0005 mg/L, copper (Cu) 0.0062 to 0.0089 mg/L, lead (Pb) 0.006 to 0.007 mg/L, zinc (Zn) 0.0247 to 0.0334 mg/L, and nickel (Ni) 0.0044 to 0.0088 mg/L. In summary, the study shows that the physical-chemical conditions of Jakarta Bay significantly affect the distribution of dissolved heavy metals such as Hg, Cu, Pb, Zn and Ni.